Modeling and simulation of acoustic propagation for mixing and pumping fluids in lab-on-a-chip devices - Catarino, Susana Oliveira (2012)
The research team is focused on lab-on-a-chip devices for clinical applications, where acoustic streaming technique is used for promoting the mixing, pumping and chemical reactions of fluids, inside the microfluidic structures. In particular, this paper focuses the modeling and simulation of the acoustic streaming generated by a piezoelectric polymer – the β-PVDF in a microchannel. The simulations are based on finite elements numerical methods and are implemented in COMSOL Multiphysics software. The modeling of acoustic streaming phenomenon includes the study of the piezoelectric effect generated by an electroactive polymer and of the compressible flow Navier-Stokes equations.